2021
DOI: 10.1136/bcr-2020-240384
|View full text |Cite
|
Sign up to set email alerts
|

Benign myoepithelioma of the soft palate: an unusual clinical entity

Abstract: Myoepitheliomas are rare benign tumours that affect the exocrine glands and are sporadically located in the salivary glands. The most common location of myoepithelioma in the oral cavity is the parotid gland and it is seldom encountered in the palate. The diagnosis of this entity is challenging since its clinical presentation may resemble those of more common neoplasms, rendering a complex histopathological diagnosis. The aim of the present case report is to describe an unusual case of myoepithelioma of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Myoepithelial cells in the salivary glands are located between the basal lamina and the acinar and ductal cells [4]. Neoplastic myoepithelial cell tumors are also found in other exocrine tissues including lacrimal glands, breast, prostate, sweat glands, vestibular mucosa, labial mucosa, nasopharynx, nasal septum, trachea, larynx, lung, esophagus, and retroperitoneum [4]. ME is a type of salivary gland tumor once considered a subtype of pleomorphic adenoma until the World Health Organization (WHO) recognized it as a distinct entity in 1991 [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Myoepithelial cells in the salivary glands are located between the basal lamina and the acinar and ductal cells [4]. Neoplastic myoepithelial cell tumors are also found in other exocrine tissues including lacrimal glands, breast, prostate, sweat glands, vestibular mucosa, labial mucosa, nasopharynx, nasal septum, trachea, larynx, lung, esophagus, and retroperitoneum [4]. ME is a type of salivary gland tumor once considered a subtype of pleomorphic adenoma until the World Health Organization (WHO) recognized it as a distinct entity in 1991 [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…ME in minor salivary glands of the oral cavity is most common on the palate [6, 7, 8]. Clinically ME presents as an asymptomatic, slowly growing tumor in the fourth and fth decades of life with no gender predilection [4,7,9,10,11]. However, an analysis of 15 patients by Cuadra et al showed a 2:1 female predilection [4,5,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations